Reconstructing America - Randolph, Joanne (Randolph, Joanne. Civil War and reconstruction: rebellion and rebuilding., 2018)
Briefly explores the post-Civil War history of the Reconstruction Era and how the Union and Confederacy came back together again after the war. Also explores the long history of the civil rights movement which began during Reconstruction. Includes a glossary.